THE ROLE OF GENETIC FACTORS IN THE DEVELOPMENT OF HERPETIC ENCEPHALITIS. A CASE FROM PRACTICE - A. S. Levina; O. V. Goleva; A. A. Vilnits; R. A. Ivanova; E. N. Suspitsin; N. V. Skripchenko; E. N. Imyanitov; E. Yu. Skripchenko (Журнал инфектологии)
.